1987
DOI: 10.1038/ki.1987.192
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of furosemide resistance in analbuminemic rats and hypoalbuminemic patients

Abstract: To elucidate the mechanism of resistance of hypoalbuminemic patients to furosemide, the effect of this diuretic on urine volume of normal and analbuminemic rats (NAR) and of hypoalbuminemic patients was studied. Intravenous administration of furosemide rapidly enhanced sodium diuresis in normal rats but not in NAR. Total plasma clearance and distribution volume of furosemide were much larger in NAR than in normal rats, while no significant difference in these pharmacokinetic parameters was observed for the unb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
5

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 12 publications
10
158
5
Order By: Relevance
“…Davison et al and Eadington et al reported positive results, but they did not perform a cross-over study or show any pharmacokinetic data (15,11). Inoue et al reported that effective diuresis was achieved by infusion of the albumin-furosemide complex in analbuminemic rats and hypoalbuminemic patients (2). All the patients in their experiment were hypoalbuminemic due to causes other than nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Davison et al and Eadington et al reported positive results, but they did not perform a cross-over study or show any pharmacokinetic data (15,11). Inoue et al reported that effective diuresis was achieved by infusion of the albumin-furosemide complex in analbuminemic rats and hypoalbuminemic patients (2). All the patients in their experiment were hypoalbuminemic due to causes other than nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 93%
“…To improve delivery of the drug, we mixed 160 mg of furosemide and 100 mL of 20% albumin solution at room temperature before administration. This method of administration was previously used by other investigators (2,16). The timing of administration of albumin and furosemide varied according to the investigators.…”
Section: Time (Hr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, infusion of the furosemide-albumin complex can increase diuretic delivery to the kidney by keeping furosemide within the vascular space. 13 However, subsequent studies found that the use of mixture of loop diuretic and albumin in hypoalbuminemic patients (secondary to cirrhosis or nephrotic syndrome), with mean plasma albumin 3.0g/ dL, produced only a modest increase in sodium excretion compared with furosemide alone without an increase in the rate of furosemide excretion.…”
Section: Furosemide-albumin Infusionmentioning
confidence: 99%